BIRTH PREPAREDNESS AND COMPLICATION READINESS AMONG PREGNANT WOMEN ATTENDING A MATERNAL AND CHILD CARE HOSPITAL OF GOVERNMENT MEDICAL COLLEGE IN SOUTH KASHMIR, INDIA: A CROSS-SECTIONAL STUDY - SALROO, FOUZIA NAZIR; NAZIR, SYED TANZEELA; GADOO, MOHSINA MUKHTAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Maternal death is an issue of great concern especially when these deaths can be prevented by appropriate management of the delays causing it. To prevent these delays, the Johns Hopkins Program for International Education in Gynecology and Obstetrics (JHPIEGO) has put forward the concept of Birth preparedness and complication readiness (BPCR). BPCR matrix comprises several core elements covering antenatal, intrapartum, postpartum, and neonatal care. Objective: The objective of the study was to assess BPCR status and its associated factors among pregnant women attending an antenatal clinic in a rural tertiary care hospital. Methods: A hospital-based cross-sectional study was conducted among 568 pregnant women attending antenatal clinic of Department of Obstetrics and Gynecology of GMC, Anantnag from October 2021 to March 2022. After giving informed consent, participants were interviewed regarding BPCR using a questionnaire adapted from the JHPIEGO. Results: BPCR index in our study was 42.34%. Almost half of the pregnant women (49.8%) were “well prepared” and remaining half (50.2%) were “less prepared”. The association between level of preparedness was statistically significant with educational status of mother (p=0.017), primi parous (p=0.04), and multiple ANC visits (p=0.014). Conclusion: Overall BPCR index was on the lower side with knowledge regarding various key danger signs, identification of a skilled health care provider and a health-care facility being very unsatisfactory.